Comments on Maria Panum Baastrup’s: invitation systems and identification in Late Iron Age southern Scandinavia? The gold foil figures from a new perspective - Lyngstrøm, Henriette (Danish Journal of Archaeology, 2016)
This commentary points out the importance of looking at apparently well-known archaeological material from new angles and highlights Maria Panum Baastrup’s work of putting gold foil figures into a functional context as an inspiring example.